2020
DOI: 10.1073/pnas.1911359117
|View full text |Cite
|
Sign up to set email alerts
|

Connectivity at the origins of domain specificity in the cortical face and place networks

Abstract: It is well established that the adult brain contains a mosaic of domain-specific networks. But how do these domain-specific networks develop? Here we tested the hypothesis that the brain comes prewired with connections that precede the development of domain-specific function. Using resting-state fMRI in the youngest sample of newborn humans tested to date, we indeed found that cortical networks that will later develop strong face selectivity (including the “proto” occipital face area and fusiform face area) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
79
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(85 citation statements)
references
References 43 publications
6
79
0
Order By: Relevance
“…However, for both tools and places, we found no effect of the time between scan and birth ("experience age") suggesting that either there was little development in this early time period in neonates, or that there are substantial individual differences that mask age effects in across-subjects analyses, but not within-subject longitudinal studies. These results extend those from fMRI 35 and functional connectivity 12 in infants and structural connectivity in adults 14 to reveal a proto-organization of category-selective regions in the ventral visual stream. The early maturity and specificity of the structural networks is further reflected in the connections identified by the classifiers.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…However, for both tools and places, we found no effect of the time between scan and birth ("experience age") suggesting that either there was little development in this early time period in neonates, or that there are substantial individual differences that mask age effects in across-subjects analyses, but not within-subject longitudinal studies. These results extend those from fMRI 35 and functional connectivity 12 in infants and structural connectivity in adults 14 to reveal a proto-organization of category-selective regions in the ventral visual stream. The early maturity and specificity of the structural networks is further reflected in the connections identified by the classifiers.…”
Section: Discussionsupporting
confidence: 76%
“…The fusiform face area (FFA) 4 , for example, receives stronger visual input from the fovea and lower spatial frequencies 11 , leading to the acquisition of representations that are particularly suited for processing faces. Recently, it was found that this proto-organization is present at 6-27 days, as a face-selective region had stronger functional connectivity with foveal V1 than peripheral V1; while the reverse was seen for a scene region 12 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is initial evidence for signatures, or precursors, of neural specialization to object categories (faces, bodies, animals and scenes), in the visual cortex of newborns or young infants, using electroencephalography [25][26][27][28] or fMRI 29,30 .…”
Section: Introductionmentioning
confidence: 99%
“…There is initial evidence for signatures, or precursors, of neural specialization to object categories (faces, bodies, animals and scenes), in the visual cortex of newborns or young infants, using electroencephalography 2528 or fMRI 29,30 . Behavioral counterparts of those neural effects include early preference for faces or face-like stimuli over inverted faces 3133 , for biological, over non-biological motion 34,35 , and for canonical, over distorted bodies 3638 .…”
Section: Introductionmentioning
confidence: 99%